2015
DOI: 10.1002/eji.201445058
|View full text |Cite
|
Sign up to set email alerts
|

Treg‐cell depletion promotes chemokine production and accumulation of CXCR3+ conventional T cells in intestinal tumors

Abstract: Additional supporting information may be found in the online version of this article at the publisher's web-site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 49 publications
8
51
0
Order By: Relevance
“…2D, we observed that the ability of CD4 + Foxp3 + Tregs to suppress the proliferation of responder CD4 + T cells was enhanced when these cells were isolated from CAC mice. This is well in line with recent studies demonstrating that Tregs isolated from human and mouse colonic tumour tissues strongly suppressed the proliferation of tumour-infiltrating CD8 + and CD4 + T cells [21, 22]. …”
Section: Resultssupporting
confidence: 77%
“…2D, we observed that the ability of CD4 + Foxp3 + Tregs to suppress the proliferation of responder CD4 + T cells was enhanced when these cells were isolated from CAC mice. This is well in line with recent studies demonstrating that Tregs isolated from human and mouse colonic tumour tissues strongly suppressed the proliferation of tumour-infiltrating CD8 + and CD4 + T cells [21, 22]. …”
Section: Resultssupporting
confidence: 77%
“…As controls, APC min/+ mice were identically treated. By day 3 and 10, at least 90% of Treg were depleted in blood, intestine and tumors of DT treated APC min/+ /DEREG [20]. Mice were killed and organs harvested on day 12.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we could demonstrate that Treg from cancer patients, but not healthy volunteers, inhibit transendothelial migration of effector T cells in vitro and that effector T cells accumulate in intestinal tumors in vivo after Treg depletion [20, 25]. In this study, our aim was to elucidate the mechanisms whereby Treg reduced the lymphocyte accumulation in tumors, with a focus on cell migration and chemokine signalling.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, diphtheria-toxinmediated FoxP3-expressing cell depletion in the Apc Min/1 mouse has been reported to increase intestinal T lymphocyte infiltrates with a proinflammatory stroma as a consequence [26]. Nevertheless, the functional significance of the CD25…”
mentioning
confidence: 99%